2021
DOI: 10.1063/5.0059464
|View full text |Cite
|
Sign up to set email alerts
|

RF surface resistance tuning of superconducting niobium via thermal diffusion of native oxide

Abstract: Recently, Nb superconducting radio frequency cavities vacuum heat treated between 300 and 400 °C for a few hours have exhibited very high quality factors (∼5 × 1010 at 2.0 K). Secondary ion mass spectrometry measurements of O, N, and C show that this enhancement in RF surface conductivity is primarily associated with interstitial O alloying via dissolution and diffusion of the native oxide. We use a theory of oxide decomposition and O diffusion to quantify previously unknown parameters crucial in modeling this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 68 publications
(63 reference statements)
8
48
0
Order By: Relevance
“…Our recent SIMS investigation [4] found elevated oxygen content near the surface of samples prepared in the similar way as Ito [1]. RF measurements of a Nb SRF cavity prepared via vacuum heat treatment at 300 °C and subsequently electropolished 180 nm to exclude any ingress of C and N demonstrated that the enhancement in quality factor is mainly due to interstitial oxygen alloying via a thermal diffusion process.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our recent SIMS investigation [4] found elevated oxygen content near the surface of samples prepared in the similar way as Ito [1]. RF measurements of a Nb SRF cavity prepared via vacuum heat treatment at 300 °C and subsequently electropolished 180 nm to exclude any ingress of C and N demonstrated that the enhancement in quality factor is mainly due to interstitial oxygen alloying via a thermal diffusion process.…”
Section: Introductionsupporting
confidence: 58%
“…RF measurements of a Nb SRF cavity prepared via vacuum heat treatment at 300 °C and subsequently electropolished 180 nm to exclude any ingress of C and N demonstrated that the enhancement in quality factor is mainly due to interstitial oxygen alloying via a thermal diffusion process. The measurements made in [4] found that the thermal diffusion process was con-sistent with Ciovati's model [5] of Nb 2 O 5 dissolution and oxygen diffusion.…”
Section: Introductionmentioning
confidence: 66%
“…The oxygen diffusion model proposed by G. Ciovati [13], qualitatively explains the diffusion of oxygen in to the rf surface of SRF cavities. The same model also describes well to the diffusion of oxygen during the mid-T heat treatment (300 -400 • C) [7].…”
Section: Introductionmentioning
confidence: 73%
“…The calculations based on the oxygen diffusion models described in Refs. [7,13] predicts the dilute oxygen concentration on the rf surface and oxygen diffuse deeper into the bulk. Even though, the final surface preparation may play some role on the initial condition of rf surface and successive baking duration, the cavity TE1-05 showed higher flux trapping sensitivity compared to cavity TE1-06.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation